The human middle ear in motion: 3D visualization and quantification using dynamic synchrotron-based X-ray imaging - Margaux Schmeltz; Aleksandra Ivanovic; Christian M. Schlepütz; Wilhelm Wimmer; Aaron K. Remenschneider; Marco Caversaccio; Marco Stampanoni; Lukas Anschuetz; Anne Bonnin (Communications Biology, 2024)
Abstract The characterization of the vibrations of the middle ear ossicles during sound transmission is a focal point in clinical research. However, the small size of the structures, their micrometer-scale movement, and the deep-seated position of the middle ear within the temporal bone make these types of measurements extremely challenging. In this work, dynamic synchrotron-based X-ray phase-contrast microtomography is used on acoustically stimulated intact human ears, allowing for the three-dimensional visualization of entire human eardrums and ossicular chains in motion. A post-gating algorithm is used to temporally resolve the fast micromotions at 128 Hz, coupled with a high-throughput pipeline to process the large tomographic datasets. Seven ex-vivo fresh-frozen human temporal bones in healthy conditions are studied, and the rigid body motions of the ossicles are quantitatively delineated. Clinically relevant regions of the ossicular chain are tracked in 3D, and the amplitudes of their displacement are computed for two acoustic stimuli.